2020
DOI: 10.1002/jcop.22365
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of peer victimization in elementary school children: Associations with changes in internalizing, externalizing, social competence, and school climate

Abstract: The current study examines the developmental changes (internalizing and externalizing symptoms, social competence, and experiences of school climate) in children who follow distinct trajectories of peer victimization in a sample of elementary school children across 2 years. Data were from children, and their parents and teachers, in Grades 1–3 followed across five waves. Latent class analyses revealed four distinct victimization trajectory groups characterized by chronically high, increasing, decreasing, or lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 57 publications
1
6
0
3
Order By: Relevance
“…As for the second hypothesis, the results confirmed that chronic victims maintained the lowest levels of social preference, perceived popularity and friendship over time, which concurs with previous cross-sectional ( Pouwels et al, 2016 ) and longitudinal studies ( Sheppard et al, 2019 , Sukhawathanakul and Leadbeater, 2020 ). The low levels of social status and friendship experienced by chronic victims highlight the situation of rejection and isolation to which they are subjected by their classmates as a group.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…As for the second hypothesis, the results confirmed that chronic victims maintained the lowest levels of social preference, perceived popularity and friendship over time, which concurs with previous cross-sectional ( Pouwels et al, 2016 ) and longitudinal studies ( Sheppard et al, 2019 , Sukhawathanakul and Leadbeater, 2020 ). The low levels of social status and friendship experienced by chronic victims highlight the situation of rejection and isolation to which they are subjected by their classmates as a group.…”
Section: Discussionsupporting
confidence: 90%
“…A growing body of research has begun to explore through longitudinal designs the differences between chronic victims, who are exposed to sustained bullying over a long period of time, and those who are bullied for a limited time ( Ouellet-Morin et al, 2020 ; Sheppard, Giletta, & Prinstein, 2019). According to these studies, chronic victims have higher levels of chronic stress, as well as externalizing and internalizing personality problems, which are not found in schoolchildren who are unaware bullying is taking place or who have suffered from bullying in a shorter or less traumatic way ( Haltigan & Vaillancourt, 2014 ; Rosen, Beron, & Underwood, 2017; Sukhawathanakul & Leadbeater, 2020 ; Sumter, Baumgartner, Valkenburg, & Peter, 2012 ).…”
mentioning
confidence: 99%
“…Pese al claro impacto que la victimización tiene en el individuo, no todos los adolescentes que lo sufren experimentan las mismas emociones y efectos negativos. La forma en que las víctimas afrontan el ciberacoso y el modo en el que gestionan dicha situación supone uno de los mayores factores diferenciales en la intensidad y persistencia de estos efectos negativos (Sheppard et al, 2019;Sukhawathanakul y Leadbeater, 2020). Efectos negativos que pueden ser más o menos perniciosos dependiendo de la variabilidad personal en el manejo de la recuperación o resiliencia.…”
Section: Resiliencia Como Potencial Mediadorunclassified
“…Las consecuencias negativas no son exclusivamente para quienes están implicados, sino para todo el alumnado, lo que ha llevado a considerar este fenómeno como un problema de salud pública (Karanikola et al, 2018). La literatura refleja con claridad que son las víctimas quienes sufren las consecuencias más negativas, en especial aquellas que viven estas experiencias de forma prolongada en el tiempo o combinada con otras experiencias de victimización (Sukhawathanakul y Leadbeater, 2020). Desafortunadamente, esta no es una situación extraordinaria.…”
Section: Introductionunclassified
“…Junto a los síntomas clínicos, las experiencias como víctima de acoso escolar también suelen provocar efectos negativos en el desempeño académico y el ajuste escolar, por ejemplo, a partir del descenso en el rendimiento académico, el aumento de las conductas absentistas, las dificultades para concentrarse en clase o la menor implicación en las tareas y actividades de aula (Fry et al, 2018). Concretamente, estos efectos negativos suelen ser más graves en las víctimas con experiencias estables de victimización (Gini et al, 2018), ya que, entre ellas, aumenta hasta en seis veces los intentos suicidas (Wang et al, 2020), hay una mayor presencia de problemas internalizantes y externalizantes, niveles más bajos de competencia social y una menor satisfacción con el clima escolar (Sukhawathanakul y Leadbeater, 2020). Asimismo, la permanencia de estas experiencias facilita la implicación en el doble rol como agresor y víctima (Sung et al, 2018), lo que genera un mayor desajuste psicosocial (Menesini et al, 2009).…”
Section: Introductionunclassified